PERAN GURU DALAM PELAKSANAAN LAYANAN BIMBINGAN KONSELING SEBAGAI PENDIDIKAN KARAKTER KREATIF PADA SISWA SECARA DARING - Lia Mareza; Siti Sarah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2023)
This study aims to determine the teacher's role in the implementation of counseling guidance services in shaping the creative character of students through online learning at SD Negeri 2 Pliken. The research method carried out by the researcher is using qualitative research methods. The study was conducted by taking 12 participants consisting of the principal, class V teacher, 5 students and their parents. Data collection techniques using observation, interviews and documentation. The results of the study indicate that the implementation of counseling guidance services in online learning uses individual and classical guidance methods using applications and blended methods. The forms of services provided to students during online learning are orientation services, content mastery services, individual counseling services, group guidance services, group counseling services, and consulting services. This form of service is provided to students through online learning through class WhatsApp groups.